2019
DOI: 10.1371/journal.pone.0209469
|View full text |Cite
|
Sign up to set email alerts
|

Which construal level combinations generate the most effective interventions? A field experiment on energy conservation

Abstract: Many campaigns targeting pro-environmental behavior combine multiple approaches without properly understanding how these different approaches interact. Here we study the effect of such combinations. We apply construal level theory to classify different intervention approaches, which can either be at a high construal level (abstract and distant) or at a low construal level (concrete and proximal). In a field experiment we recruited 197 students living in one-person apartments in an all-inclusive student housing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
7
1
1
Order By: Relevance
“…These results suggest the limited use of the construal level in predicting pro-environmental behaviors. Moreover, contrary to the expected results, the study of Griffioen et al (2019) showed that a high social distance condition was correlated with high construal levels which had a greater effect on mitigation behaviors. For these reasons, the existence of the relation among psychological distance and construal levels is not always obvious, especially in the situation of climate change and related adaptation and mitigation behaviors.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…These results suggest the limited use of the construal level in predicting pro-environmental behaviors. Moreover, contrary to the expected results, the study of Griffioen et al (2019) showed that a high social distance condition was correlated with high construal levels which had a greater effect on mitigation behaviors. For these reasons, the existence of the relation among psychological distance and construal levels is not always obvious, especially in the situation of climate change and related adaptation and mitigation behaviors.…”
Section: Discussioncontrasting
confidence: 78%
“…This is especially relevant because the impacts of climate change may differ between different geographical territories and may consequently be perceived differently. The description of results for each study is divided into three paragraphs based on environmental behavior: two studies explored the role of psychological distance in the commitment to adaptation behavior toward climate change (Niles et al, 2015;Singh et al, 2017); 10 studies focused on engagement in mitigation with reference to some dimensions of psychological distance and climate change (Spence et al, 2012;Busse and Menzel, 2014;Milfont et al, 2014;Carmi and Kimhi, 2015;Jones et al, 2017;Soliman et al, 2018;Chen et al, 2019;Griffioen et al, 2019;Kim and Ahn, 2019;Kyselá et al, 2019); seven studies analyzed the link between psychological distance and each dimension with mitigation and adaptation behaviors applied to climate change (Haden et al, 2012;Brügger et al, 2015aBrügger et al, , 2016Rickard et al, 2016;Schuldt et al, 2018;de Guttry et al, 2019;Wang et al, 2019).…”
Section: Results Of Studiesmentioning
confidence: 99%
“…La distance psychologique pour comprendre l'écart entre attitudes et comportements prosociaux du consommateur White et al (2019) ont souligné l'écart existant entre les attitudes prosociales du consommateur et son comportement effectif. L'une des raisons qui expliquent cette différence est liée à la distance psychologique expérimentée avec des causes environnementales telles que le changement climatique (Brügger, 2020 ;Brügger et al, 2015 ;Spence et Pidgeon, 2010 ;Spence et al, 2012), la pollution (Zhang et al, 2014, la réduction du gaspillage (Barnes, 2019 ;Guillard, 2019 ), l'utilisation raisonnée des énergies (Griffioen et al, 2019 ;Tangari et Smith, 2012 ;Tangari et al, 2015) ou encore le recyclage (Schill et Schaw 2016 ;White et al, 2011).…”
Section: La Distance Psychologique Pour éClairer Le Comportement Du Consommateurunclassified
“…White et al ( 2019) have highlighted the gap between consumers' prosocial attitudes and their actual behavior. One reason for this difference is related to the psychological distance experienced with environmental causes such as climate change (Brügger, 2020;Brügger et al, 2015;Spence et al, 2012;Spence and Pidgeon, 2010), pollution (Zhang et al, 2014), waste reduction (Barnes, 2019;Guillard, 2019), sensible energy use (Griffioen et al, 2019;Tangari et al, 2015;Tangari and Smith, 2012), and recycling (Schill and Schaw, 2016;White et al, 2011). Understandably, when consumers feel psychologically distant from an environmental cause (e.g.…”
Section: Using Psychological Distance To Understand the Gap Between The Consumer's Attitudes And Prosocial Behaviormentioning
confidence: 99%